The power of a smile: Stronger working memory effects for happy faces in adolescents compared to adults. Issue 2 (17th February 2016) - Cromheeke, Sofie; Mueller, Sven C.
Abstract : Theories of adolescent behaviour attribute increases in risk-taking and sensation-seeking in this age group to a heightened sensitivity to emotional stimuli on the one hand and a relatively immature cognitive control system on the other hand. However, little research has outlined to what extent relevant and irrelevant emotional stimuli bias the imbalance between affective processing and cognitive control. Thirty-three adolescents (19 females, aged 12–14) and 37 adults (18 females, aged 18–29) completed two attentional conditions of an emotional face working memory (WM) 0-back/2-back task. Participants were asked to attend to the emotional facial expression in the "relevant" emotion condition, and to the gender of the face in the "irrelevant" condition. The results revealed a WM improvement for happy faces in the relevant condition in both age groups, and an impairment for irrelevant happy faces in adolescents, but not adults. Furthermore, the difference between both attentional conditions for happy faces was larger in adolescents than adults. Results are discussed within the framework of theories of adolescent behaviour.